Kandungan Gizi dan Manfaat Air Kelapa terhadap Metabolisme Diabetes: Kajian Naratif: Nutritional Content and Benefits of Coconut Water for the Diabetes Metabolism: a Narrative Review - Jeallyza Muthia Azra; Budi Setiawan; Zuraidah Nasution; Ahmad Sulaeman; Sri Estuningsih (Amerta Nutrition, 2023)
Background: Coconut water is one of the natural food products that is widely available around the world. This commodity provides nutritional content that could increase rehydration status and improve health. The application of coconut water to health, including improving type 2 diabetes metabolism, has gotten research interest in recent years. Objectives: This narrative review paper aimed to summarize several articles about the nutritional content and the mechanism of the potential bioactive component in coconut water to improve type 2 diabetes metabolism. Methods: This study design was a narrative review of several articles from five databases search: PubMed/MEDLINE, Scielo, PsycINFO, Microsoft Academic, and Google Scholar. Discussion: Coconut water includes several biologically active components such as protein, amino acid, fatty acid, mineral, vitamin, and phenolic compounds. The recent discovery of nutrient content, especially antioxidant properties, and arginine in coconut water, signifies a good potential in improving type 2 diabetes mellitus. Antioxidant and arginine altered blood glucose, glycated hemoglobin, serum creatinine, blood urea, albumin, albumin/globulin ratio, liver function enzyme, lipid profile, antioxidant status, and lipid peroxidation without any significant hepatocellular damage. Arginine enhanced the nitric oxide synthase activity in the liver and arginine levels in the plasma. In mammals, the arginine-nitric oxide system, which includes AMPK, cGMP, PGC-1α, and PI3K, can maintain blood glucose homeostasis, increase insulin sensitivity, and prevent diabetes-induced oxidative stress. Conclusion: Coconut water can help to improve metabolism in type 2 diabetes mellitus conditions through antioxidant activity and arginine content.